DISCRIMINANT ANALYSIS IN DETERMINING THE DIFFERENTIATING FACTORS OF BLENDED LEARNING SUCCESS IN EDUCATIONAL INSTITUTIONS - Kurniawan, Heri; Warsihna, Jaka (Universitas Terbuka, 2023)
Blended learning has become an increasingly popular approach in the educational field because it combines traditional/conventional learning with digital technology-based learning. However, the success of implementing blended learning in educational institutions can be influenced by various different factors depending on the characteristics of the educational institution. Therefore, this study aims to analyze the differentiating factors that influence the success of blended learning in educational institutions. The discriminant analysis method in this study was used to identify and determine the differentiating factors that distinguished the high success blended learning group from the low success group. Research data was collected from various educational institutions that have implemented blended learning in their curricula. The results of the analysis show that there are several significant differentiating factors between the high and low success groups in applying blended learning. Some of these factors include Implementation Standards and Guidelines, Infrastructure and Technology mastery, Learning Strategy, Human Resources, Learning Content and Learning Environment. This research makes an important contribution to the development of more effective blended learning implementation strategies in educational institutions. By understanding the differentiating factors that influence success, educational institutions can increase their efforts to create a conducive learning environment and improve the quality of student learning outcomes.